Appropriate Circadian-Circasemidian Coupling Protects Blood Pressure from Morning Surge and Promotes Human Resilience and Wellbeing - Otsuka K; Murakami S; Okajima K; Shibata K; Kubo Y; Gubin DG; Beaty LA; Cornelissen G (Clinical Interventions in Aging, 2023)
Kuniaki Otsuka,1,2 Shougo Murakami,3 Kiyotaka Okajima,4 Koichi Shibata,1 Yutaka Kubo,5 Denis G Gubin,6– 8 Larry A Beaty,2 Germaine Cornelissen2 1Tokyo Women’s Medical University, Tokyo, Japan; 2Halberg Chronobiology Center, University of Minnesota, Minneapolis, MN, USA; 3Department of Cardiovascular Medicine, Soseikai General Hospital, Kyoto, Japan; 4Cardiovascular Internal Medicine, Higashi Omiya General Hospital, Saitama, Japan; 5Department of Medicine, Machida Keisen Hospital, Tokyo, Japan; 6Laboratory for Chronobiology and Chronomedicine, Research Institute of Biomedicine and Biomedical Technologies, Medical University, Tyumen, 625023, Russia; 7Department of Biology, Medical University, Tyumen, 625023, Russia; 8Tyumen Cardiology Research Center, Tomsk National Research Medical Center, Russian Academy of Science, Tomsk, RussiaCorrespondence: Germaine Cornelissen, Halberg Chronobiology Center, University of Minnesota, MMC8609, 420 Delaware Street SE, Minneapolis, MN, 55455, USA, Email corne001@umn.edu.an Kuniaki Otsuka, Executive Medical Center, Totsuka Royal Clinic, Tokyo Women’s Medical University, Related Medical Facility, Sinjuku City, Tokyo, Japan, Email frtotk99@ba2.so-net.ne.jpBackground: Blood pressure (BP) variability is involved in the appraisal of threat and safety, and can serve as a potential marker of psychological resilience against stress. The relationship between biological rhythms of BP and resilience was cross-sectionally assessed by 7-day/24-hour chronobiologic screening in a rural Japanese community (Tosa), with focus on the 12-hour component and the “circadian-circasemidian coupling” of systolic (S) BP.Subjects and Methods: Tosa residents (N = 239, 147 women, 23– 74 years), free of anti-hypertensive medication, completed 7-day/24-hour ambulatory BP monitoring. The circadian-circasemidian coupling was determined individually by computing the difference between the circadian phase and the circasemidian morning-phase of SBP. Participants were classified into three groups: those with a short coupling interval of about 4.5 hours (Group A), those with an intermediate coupling interval of about 6.0 hours (Group B), and those with a long coupling interval of about 8.0 hours (Group C).Results: Residents of Group B who showed optimal circadian-circasemidian coordination had less pronounced morning and evening SBP surges, as compared to residents of Group A (10.82 vs 14.29 mmHg, P < 0.0001) and Group C (11.86 vs 15.21 mmHg, P < 0.0001), respectively. The incidence of morning or evening SBP surge was less in Group B than in Group A (P < 0.0001) or Group C (P < 0.0001). Group B residents showed highest measures of wellbeing and psychological resilience, assessed by good relation with friends (P < 0.05), life satisfaction (P < 0.05), and subjective happiness (P < 0.05). A disturbed circadian-circasemidian coupling was associated with elevated BP, dyslipidemia, arteriosclerosis and a depressive mood.Conclusion: The circadian-circasemidian coupling of SBP could serve as a new biomarker in clinical practice to guide precision medicine interventions aimed at achieving properly timed rhythms, and thereby resilience and wellbeing.Keywords: 7-day/24-hour chronobiologic screening, blood pressure, biological 12-hour rhythm, appropriate circadian-circasemidian coupling, circadian acrophase, 12-hour morning acrophase, morning blood pressure surge, evening blood pressure surge, human resilience, wellbeing